Hollow MnO2 as a tumor-microenvironment-responsive biodegradable nano-platform for combination therapy favoring antitumor immune responses. Issue 1 (December 2017) - Yang, Guangbao; Xu, Ligeng; Chao, Yu; Xu, Jun; Sun, Xiaoqi; Wu, Yifan; Peng, Rui; Liu, Zhuang
Abstract Herein, an intelligent biodegradable hollow manganese dioxide (H-MnO2 ) nano-platform is developed for not only tumor microenvironment (TME)-specific imaging and on-demand drug release, but also modulation of hypoxic TME to enhance cancer therapy, resulting in comprehensive effects favoring anti-tumor immune responses. With hollow structures, H-MnO2 nanoshells post modification with polyethylene glycol (PEG) could be co-loaded with a photodynamic agent chlorine e6 (Ce6), and a chemotherapy drug doxorubicin (DOX). The obtained H-MnO2 -PEG/C&D would be dissociated under reduced pH within TME to release loaded therapeutic molecules, and in the meantime induce decomposition of tumor endogenous H2 O2 to relieve tumor hypoxia. As a result, a remarkable in vivo synergistic therapeutic effect is achieved through the combined chemo-photodynamic therapy, which simultaneously triggers a series of anti-tumor immune responses. Its further combination with checkpoint-blockade therapy would lead to inhibition of tumors at distant sites, promising for tumor metastasis treatment. MnO2 nanostructures are promising TME-responsive theranostic agents in cancer. Here, the authors develop a nano-platform based on hollow H-MnO2 nanoshells able to modulate the tissue microenvironment, release a drug and inhibit tumor growth alone or in combination with check-point blockade therapy.